2006
DOI: 10.1086/503873
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Modulation of the Innate Immune Response in Feline Immunodeficiency Virus–Infected Cats

Abstract: Lentivirus infection impairs innate immune function in vivo, and IL-15 can significantly restore function. We hypothesize that altered dendritic-cell function and increased regulatory T cell activity may underlie the innate immune defect in HIV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 49 publications
2
14
0
Order By: Relevance
“…We have previously shown that chronically and acutely FIV-infected cats have an impaired innate immune response to the intracellular pathogen Lm [12],[13]. Here we showed that 3 days post-Lm challenge, chronically FIV-infected animals had a greater number of Lm colony-forming units per LN than SPF-control cats (64,280±31,253; 5,318±3,878 CFU/LN respectively, mean ± SEM).…”
Section: Resultssupporting
confidence: 50%
See 2 more Smart Citations
“…We have previously shown that chronically and acutely FIV-infected cats have an impaired innate immune response to the intracellular pathogen Lm [12],[13]. Here we showed that 3 days post-Lm challenge, chronically FIV-infected animals had a greater number of Lm colony-forming units per LN than SPF-control cats (64,280±31,253; 5,318±3,878 CFU/LN respectively, mean ± SEM).…”
Section: Resultssupporting
confidence: 50%
“…We previously reported that FIV-infected cats have an impaired innate response that fails to gain initial control of bacterial replication prior to the adaptive immune response [12]. We also demonstrated that locally delivered IL-15, a cytokine known to activate and stimulate NK cell proliferation, cytolytic activity, and cytokine and chemokine production, significantly restored innate immune function as measured by Lm clearance [13]. Here, we show that compared to SPF-control cats, NK cells from chronically FIV-infected cats have a constitutively higher level of proliferation that is counter-balanced by increased apoptosis.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…These data suggest that FIV-induced immunodeficiency may be derived from a failure to generate an IL-12 dependent response, in part due to elevated levels of IL10, which is known to suppress IL12 production by dendritic cells. In a more recent study, Dean et al (2006) reported a significant increase in bacterial numbers in FIV + cats compared to control cats as early as one day following L. monocytogenes infection, suggesting a poor innate immune response in the FIV + cats. In support of this, addition of IL15 increased NK activity and dramatically decreased the bacterial counts in co-infected cats (Dean et al, 2006).…”
Section: Cytokine Dysregulationmentioning
confidence: 95%
“…In a more recent study, Dean et al (2006) reported a significant increase in bacterial numbers in FIV + cats compared to control cats as early as one day following L. monocytogenes infection, suggesting a poor innate immune response in the FIV + cats. In support of this, addition of IL15 increased NK activity and dramatically decreased the bacterial counts in co-infected cats (Dean et al, 2006). In summary, although a clear TH1 to TH2 shift does not occur in FIV infection, the cytokine dysregulation leads to suppressed innate and CMI responses, resulting in the inability of an FIV + cat to mount a primary immune response to a secondary pathogen.…”
Section: Cytokine Dysregulationmentioning
confidence: 95%